Intervensi Edukasi Digital Marketing untuk Peningkatan Pengetahuan Siswa Siswi Madrasah Aliyah - Nasri, Muhammad Haris; Hammad, Rifqi; Husaini, Rahayun Amrullah; Roodhi, Mohammad Najid; Pratama, Gede Yogi (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
Advances in digital technology require young people to possess adequate digital literacy skills, particularly in digital marketing, which is now a crucial skill in education, the workplace, and entrepreneurship. However, observations indicate that Madrasah Aliyah (MA) students still lack a grasp of digital marketing concepts and practices. This community service activity aims to improve MA students' knowledge and understanding of basic digital marketing concepts, social media promotion strategies, digital branding principles, and consumer behavior in the digital world. The activity is divided into three stages: preparation, implementation, and evaluation. The preparation phase includes initial discussions with schools and the development of training materials. During the implementation phase, materials are delivered through interactive lectures and discussions, followed by simple practices using digital platforms. Assessments were conducted using pre- and post-tests to measure student knowledge gains. The results showed significant improvement, with an average pre-test score of 42.7 rising to 82.4 in the post-test. This 39.7-point increase indicates that the training successfully strengthened students' understanding of digital marketing concepts. This activity is effective in improving MA students' digital literacy and is relevant to continue with mentoring to better prepare them to face the challenges of the digital era